Integrative Phylogenomics of Amphibian Clades (Zoological Archives: An International Journal, 2026)
Amphibians comprise the most threatened vertebrate class, yet the deep phylogenetic relationships among majoramphibian clades -- and the timing of their major diversification events -- remain incompletely resolved, limitingcomparative analyses of the biological traits that predict vulnerability and the evolutionary origins of susceptibility tochytridiomycosis. This study assembled a phylogenomic dataset of 3,240 ultraconserved element (UCE) loci and 284single-copy nuclear genes from 124 amphibian species representing all three orders (Gymnophiona: 18 species;Caudata: 48 species; Anura: 58 species) plus 16 tetrapod outgroups, including 28 newly sequenced transcriptomes fromtaxonomically critical lineages. Concatenated maximum likelihood (IQ-TREE; 4,924,840 bp supermatrix) and coalescentspecies tree analyses (ASTRAL-III; 3,240 gene trees) converged on a well-supported topology resolving Gymnophionaas sister to Batrachia (Caudata + Anura; bootstrap 98%, gCF = 64.8%). Relaxed clock divergence time estimation(MCMCtree; 22 fossil calibrations) placed the Lissamphibia crown at 324 +/- 14 Ma and recovered a Triassic origin of allthree modern orders (Gymnophiona 248 +/- 12 Ma; Caudata 234 +/- 10 Ma; Anura 218 +/- 10 Ma). Concordance factoranalysis identified 8 nodes with gene tree discordance attributable to incomplete lineage sorting during rapidCretaceous-Paleogene diversification. Ancestral state reconstruction identified direct development (loss of free-livinglarval stage) as having evolved independently at least 14 times within Anura, with strong correlation with terrestrialmicrohabitat specialisation. These results provide the most comprehensively resolved amphibian phylogeny to date anda dated framework for macroevolutionary analyses of amphibian diversification, trait evolution, and vulnerability toextinction.